2018
DOI: 10.1186/s12913-018-3146-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-directed self-management of pain (PaDSMaP) compared to treatment as usual following total knee replacement; a randomised controlled trial

Abstract: BackgroundSelf-administration of medicines by patients whilst in hospital is being increasingly promoted despite little evidence to show the risks and benefits. Pain control after total knee replacement (TKR) is known to be poor.The aim of the study was to determine if patients operated on with a TKR who self-medicate their oral analgesics in the immediate post-operative period have better pain control than those who receive their pain control by nurse-led drug rounds (Treatment as Usual (TAU)).MethodsA prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…By comparing the postoperative VAS scores and trend changes of patients in the resting state and in the exercise state, the results showed that the median postoperative VAS score in group F was 2 (1) at 8 h, 12 h, and 24 h after the operation in the exercise state. ,2), 3(2,3) and 4(2,4) and the median VAS scores of group S 2(2,2), 3(2,3) and 4(3,5) compared with group C VAS e median scores of 3(2,3), 4(4,5) and 5 (3,6) were significantly reduced (p < 0.05). Table 5 shows the comparison of the VAS scores of the three groups of patients in the postoperative exercise state.…”
Section: Comparison Of Postoperative Analgesia In Patientsmentioning
confidence: 87%
See 1 more Smart Citation
“…By comparing the postoperative VAS scores and trend changes of patients in the resting state and in the exercise state, the results showed that the median postoperative VAS score in group F was 2 (1) at 8 h, 12 h, and 24 h after the operation in the exercise state. ,2), 3(2,3) and 4(2,4) and the median VAS scores of group S 2(2,2), 3(2,3) and 4(3,5) compared with group C VAS e median scores of 3(2,3), 4(4,5) and 5 (3,6) were significantly reduced (p < 0.05). Table 5 shows the comparison of the VAS scores of the three groups of patients in the postoperative exercise state.…”
Section: Comparison Of Postoperative Analgesia In Patientsmentioning
confidence: 87%
“…e purpose of Deane's study is to determine whether patients undergoing TKR surgery who self-administer oral analgesics immediately after surgery have better pain control (treatment as usual) than patients who receive pain control through a nurse-led medication round (TAU). A prospective, parallel design, open-label, and randomized controlled trial compared patient-guided pain self-management after TKR and nurse-controlled oral analgesia (TAU) for pain control [3]. Although the research perspective is forward-looking, there are still many unachievable parts of the technology.…”
Section: Related Workmentioning
confidence: 99%
“…It can be the start for enhancing skills needed for effective self-management, such as problem solving, decision making, self-monitoring and symptom management, and for developing a behavior change action plan [3,8]. In addition, patients can be prepared prior to hospitalization to perform selfmanagement before, during and after hospitalization [32][33][34].…”
Section: Discussionmentioning
confidence: 99%